The Professional Level and its Impact on Muscle Mechanical and Functional Performance in Costa Rican Soccer Players - Rojas-Valverde, Daniel (2023)
This study aimed to compare the mechanical and functional muscle performance of three different competitive soccer teams of the Costa Rica professional league (U17, Pro A, and Pro B). Age 20.09 ± 4.32 years old, weight body mass 70.85 ± 7.45 kg, height 174.56 ± 4.97 cm; body fat percentage 13.9 ± 5.06 %; lean body mass 57.90 ± 4.88 kg; lean body mass right lower limb 10.11 ± 0.87 kg; lean body mass left lower limb 10.09 ± 0.92 kg. The variables assessed were muscle time of contraction, muscle radial displacement, delay time, squat jump, and countermovement jump. The devices used were dual ray absorptiometry, tensiomyography, and jump platform. There were differences in weight, body mass, and body fat % (Pro A< U17<Pro B). There was a difference in group squat jump performance (Pro A> U17). There were no significant differences in muscle time of contraction, delay time, or radial deformation. The knowledge of differences in both muscle functional and mechanical performance could lead to new training and recovery methods and protocols considering the player’s professional levels.